Islamic Banking Literacy in the Understanding of the Muslim Community of Kadujaya Village Toward Islamic Bank Products - Didi Suardi; Topan; Ade Muslimat; Fatkhur Rohman; Oom Komariyah (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Purpose – This study aims to analyze Islamic banking literacy among the Muslim community of Kadujaya Village in relation to their understanding of Islamic bank products. This issue is relevant because limited knowledge of Islamic banking principles, contracts, and products remains a major obstacle to strengthening Islamic financial inclusion, particularly in communities where conventional banking practices are still dominant. Design/Methods/Approach – This study employed a descriptive qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving ten community informants from Kadujaya Village, RT 002/RW 008, and one expert informant. The data were analyzed through data collection, data reduction, data display, and conclusion drawing. Findings – The findings show that the Muslim community’s understanding of Islamic banking remains limited. Informants generally understood Islamic banks as financial institutions that do not apply interest, but they did not yet have a comprehensive understanding of operational principles, contracts, profit-sharing mechanisms, or the variety of Islamic banking products. Research Implications/Limitations – This study implies the need for more contextual, sustainable, and community-based Islamic banking education. However, the study is limited to a small number of informants in one village community, so the findings cannot be generalized to all Muslim communities. Originality/Value – This study contributes to Islamic banking literacy research by focusing on the understanding of Islamic banking among village-level Muslim communities and identifying factors that influence Islamic financial literacy.